Does Attending Surgeon Presence at the Preinduction Briefing Improve Operating Room Efficiency?. (23rd July 2019) - Saxena, Rajeev C.; Whipple, Mark E.; Neradilek, Moni B.; Solomon, Stuart; Fong, Christine T.; Nair, Bala G.; Lang, John D.
Abstract : Objective: To examine if attending surgeon presence at the preinduction briefing is associated with a shorter time to incision. Study Design: Retrospective cohort study and survey. Setting: Tertiary academic medical center. Subjects and Methods: A retrospective cohort study was conducted of 22, 857 operations by 141 attending surgeons across 12 specialties between August 3, 2016, and June 21, 2018. The independent variable was attending surgeon presence at the preinduction briefing. Linear regression models compared time from room entry to incision overall, by service line, and by surgeon. We hypothesized a shorter time to incision when the attending surgeon was present and a larger effect for cases with complex surgical equipment or positioning. A survey was administered to evaluate attending surgeons' perceptions of the briefing, with a response rate of 68% (64 of 94 attending surgeons). Results: Cases for which the attending surgeon was present at the preinduction briefing had a statistically significant yet operationally minor reduction in mean time to incision when compared with cases when the attending surgeon was absent. After covariate adjustment, the mean time to incision was associated with an efficiency gain of 1.8 ± 0.5 minutes (mean ± SD; P <. 001). There were no statistically significant differences in the subgroups of complex surgical equipment and complex positioning or in secondary analysis comparing service lines. The surgeon was the strongest confounding variable. Survey results demonstrated mild support: 55% of attending surgeons highly prioritized attending the preinduction briefing. Conclusion: Attending surgeon presence at the preinduction briefing has only a minor effect on efficiency as measured by time to incision.